2013
DOI: 10.3758/s13414-013-0533-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender membership on sequential decisions of face attractiveness

Abstract: Responses in a current trial are biased by the stimulus and response in the preceding trial. In a mixed-category sequence, the sequential dependency is weaker when the stimuli of the current and preceding trials fall under different categories. In the present study, we investigated the influence of the gender membership of faces on the sequential dependency. Forty-eight pictures of male and female faces were presented successively. Participants rated the attractiveness, roundness, or intelligence of each face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 25 publications
8
37
0
1
Order By: Relevance
“…The first result ( β 2 ) parallels the assimilative bias seen by Kondo et al (2012; 2013), but extends it by showing that this bias can be linked to the previous response rather than to the attractiveness of the previous face. Notably, this response bias occurs across judgment types: hair darkness ratings influence attractiveness ratings.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The first result ( β 2 ) parallels the assimilative bias seen by Kondo et al (2012; 2013), but extends it by showing that this bias can be linked to the previous response rather than to the attractiveness of the previous face. Notably, this response bias occurs across judgment types: hair darkness ratings influence attractiveness ratings.…”
Section: Resultssupporting
confidence: 60%
“…if the previous face was very attractive, the current face will be rated as less attractive than usual) (Cogan et al, 2013; Wedell et al, 1987), other studies report an assimilative effect (i.e. if the previous face was very attractive, the current face will be rated as more attractive than usual) (Kondo et al., 2012; Kondo, Takahashi, & Watanabe, 2013). In this paper, we make use of a novel experimental paradigm to resolve this apparent contradiction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested a positive correlation between subjects' attractiveness ratings of the presented facial image and the previous facial image (Kondo et al, 2012, 2013; Kramer, Jones, & Sharma, 2013). This positive correlation could be the result of sequentially dependent attractiveness perception or sequentially dependent response bias (Pegors et al, 2015).…”
Section: General Discussion and Conclusionmentioning
confidence: 90%
“…Whether and how the visual system promotes perceived object continuity over time remains an important question. Recent experiments have demonstrated a serial dependence in perception: a bias in the perceived identity of objects toward similar objects seen in the last few seconds (Cicchini, Anobile, & Burr, 2014; Fischer & Whitney, 2014; Kondo, Takahashi, & Watanabe, 2012, 2013; Liberman, Fischer, & Whitney, 2014; Taubert, Van der Burg, & Alais, 2016b). Intriguingly, visual processing may mirror the temporal regularity of objects in the physical world through a perceptual bias that promotes stability of identity perception.…”
Section: Introductionmentioning
confidence: 99%